2000
DOI: 10.1002/(sici)1097-4636(2000)53:2<181::aid-jbm8>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

The piezoelectric cochlear implant: Concept, feasibility, challenges, and issues

Abstract: A better understanding of the fundamental phenomena occurring in both the healthy and the artificially stimulated cochlea will greatly aid in the engineering of more effective cochlear implant devices and will, in general, enhance mankind's knowledge of inner ear function. This study was initiated to probe the feasibility of use of artificial piezoelectric transducer devices, both for the understanding of cochlear phenomena and as a possible cochlear implant. Aspects of feasibility of such an implant, the issu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…A bio-inspired auditory sensor or an artificial basilar membrane that mimics the biological cochlea is the most promising solution for an advanced totally implantable cochlear implant. (6)(7)(8)(9)(10) It replaces the external microphone and speech processor with one tiny mechanical sensor, while maintaining a low-power consumption and a compact size. The bio-inspired auditory sensor based on the piezoelectric principle produces electrical signals of multiple channels in response to the spectrum of acoustic inputs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A bio-inspired auditory sensor or an artificial basilar membrane that mimics the biological cochlea is the most promising solution for an advanced totally implantable cochlear implant. (6)(7)(8)(9)(10) It replaces the external microphone and speech processor with one tiny mechanical sensor, while maintaining a low-power consumption and a compact size. The bio-inspired auditory sensor based on the piezoelectric principle produces electrical signals of multiple channels in response to the spectrum of acoustic inputs.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, we found that many people used sensors that stimulate auditory nerves directly. (6,7) However, such sensors cannot produce charge-balanced electrical signals to stimulate auditory nerves in response to the same acoustic inputs regardless of their position, material, and geometric structure, which might lead to safety issues. (3) Hence, we proposed the use of output signals of the sensor, not as auditory nerve stimulators but as an ultra low-noise and ultra low-power digital signal processor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of a working piezoelectric cochlear implant poses serious challenges for piezoelectric materials. Current piezoelectric materials have not sufficient properties so that the generated charge can't stimulate the nerves, without any need for amplification [2]. Several researchers carried out various studies on the artificial basilar membrane mimicking structure and function of human cochlea.…”
Section: Introductionmentioning
confidence: 99%
“…At present there is an increasing need for small sized high sensitivity devices for various applications. The feasibility of a piezoelectric device based cochlear implant has recently been discussed by two of the authors [3] and polymer piezoelectric devices utilizing bending (flexure) mode piezoelectricity have been proposed [4,5]. Bending mode piezoelectricity [4,6,7] offers very high sensitivity and the effect is described by the following equation [4,7]:…”
Section: Introductionmentioning
confidence: 99%